HUBUNGAN PEMBINGKAIAN INFORMASI ANGGARAN, PERTANGGUNGJAWABAN DAN PENGALAMAN TERHADAP KEPUTUSAN INVESTASI - Al, M; Ariyanti, Ariyanti (Jurnal Analisis Bisnis Ekonomi, 2008)
This purpose of this studtis to investigate the relation among variable of frame budgeting information, responbility and experience of investation decision. This sample research is 50 accounting student in Magelang Muhammadiyah University. The study is conducted in an experimental setting and the method or primary data obtained from perception of all responden to questions of where questionnaires distributed directly. The result of study provide initial evidence that the different obtained of decision traits for risk investation if the information is negative framed and Ha information is positive framed with significantly is 5%, and the different obtained of personal decision trais between of the men and the women with the top responbility conditions and the low responbility conditions and that decisions besarnya keputusan, is effected by groups or the person experiences in project. This is obtaines of ? = 0.758 with significantly is 0.000 but to gender is not effect in the decision making to investation.